Morphological characteristics of bone marrows in patients with SARS-COV-2 infection from Hospital 2 de Mayo, Peru - Pichardo-Rodríguez, Rafael (2021)
Background: It has been described that, at the medullary level, SARS-COV2 can compromise hematopoiesis, manifesting with cytopenias and there are only studies carried out in autopsies. Objective: to describe the morphological characteristics of the bone marrow of patients hospitalized for COVID-19 pneumonia at the Hospital Nacional “Dos de Mayo”. Material and methods: Retrospective cross-sectional observational study carried out in patients over 18 years of age with a confirmed diagnosis of COVID-19 by rapid or molecular testing, and those with incomplete, illegible or missing medical history and / or bacterial or fungal pneumonia were excluded. The findings of the bone marrow readings were confirmed by a trained hematologist, collecting data such as: hemosiderin, cellularity, myelo / erythroid ratio, myeloid series, megakaryocytic and plasma cells. Descriptive statistics based on frequencies and percentages were used for qualitative variables and mean and standard deviation for quantitative variables. Results: A total of 30 patients were included. The most frequent marrow findings were: macrophages with cytophagocytosis in 87% (n = 26), hyperplasia with arrest in the maturation of myeloid progenitors in 70% (n = 21). 87% (n = 26) of the samples presented eosinophilia. No or little evidence of platelet formation was observed in 57% (n = 17) of the samples. In 40% (n= 12) 6% of plasma cells were found. Conclusion: Patients with SARS-COV2 infection present medullary alterations, among which are: cytophagocytosis with hyperplasia and maturation arrest in the myeloid series, little or no platelet production in megakaryocytes and eosinophilia.